Cegos rabequeiros cantadores of Northeast Brazil: Manifestation of the Blind Poet-Singer and Blind Fiddler Archetypes (Revista Música, 2023)
This article addresses the poetic, musical universe of cegos rabequeiros cantadores [blind singing fiddlers] in Northeast Brazil. These performers expressed themselves through a poetics in which their circumstances as men deprived of vision and their instruments became themes that inspired their artistic creations. Such a manifestation incorporated the archetypes of the blind poet-singer and the blind fiddler, widely diffused both geographically and historically, as do the poetic, musical elements of two traditional figures from the same region: the blind man who begs for alms while singing and the northeastern cantador [singer]. Most of these rabequeiros depended on handouts to survive, begging in exchange for songs accompanied by the rabeca [Brazilian fiddle].